'Faking brands': Consumer responses to counterfeiting. Issue 3 (7th December 2012) - Hamelin, Nicolas; Nwankwo, Sonny; El Hadouchi, Rachad
ABSTRACT Whilst counterfeiting is regarded as one of the 'oldest crimes in history', contextualised treatments of Middle East and North Africa (MENA region) are rare despite growing interconnections with the global economy. Accordingly, this paper explores consumer motivations to purchase counterfeit products and identifies possible counter‐influences. Data from a survey of 400 respondents drawn from Morocco was tested with logistic regression models to determine the significant factors that trigger responsiveness and deterrence to counterfeit products. The tests were based on three product categories: clothing, cosmetics and mobile phones. Additionally, consumer demographics and selected social triggers were evaluated to build a profile of consumers typically likely to consider buying (or avoiding) counterfeit goods. Results show that concerns related to health, disappointment risk and integrity are the most significant countervailing factors on behavioural intentions towards purchasing counterfeits. On a socio‐demographic level, it was found that low‐income consumers are more positively disposed to buying counterfeits. Gender also seems to have an explanatory force. Women with higher educational backgrounds are less likely than men to consider buying counterfeit goods. For all the products evaluated, quality and price consistently proved the most important factors driving the intention to buy counterfeits. The implications are highlighted; combating counterfeiting is not an exclusive preserve of any single entity (governments, business or para‐governmental agencies) but a shared responsibility. There is a lot at stake for consumers, manufacturers and the industrial nations if the menace is not effectively checked. Copyright © 2012 John Wiley & Sons, Ltd.